Effect of Contact-Based Interventions on Stigma and Discrimination: A Critical Examination of the Evidence - Jorm, Anthony F (Psychiatric services (Washington, D.C.), 2020)
Contact-based interventions are commonly regarded as best practice in stigma reduction. In this Open Forum, the author used the findings from eight systematic reviews to critically evaluate the quality of the evidence for the effectiveness of such interventions. He found that trials of contact-based interventions lacked methodological rigor, reporting was biased toward positive results, the trials were subject to demand characteristics, no dose effects were observed, effects did not last, and no evidence supported behavior change. Standards for future trials are proposed and implications for reducing stigma and discrimination are discussed.